2021
DOI: 10.1007/s11136-021-03070-2
|View full text |Cite
|
Sign up to set email alerts
|

Social support and health-related quality of life among the oldest old — longitudinal evidence from the multicenter prospective AgeCoDe-AgeQualiDe study

Abstract: Purpose The aim of this study was to examine the longitudinal within-association between social support and health-related quality of life among the oldest old. Methods Longitudinal data (follow-up waves 7 to 9) were used from the multicenter prospective cohort study “Needs, health service use, costs and health-related quality of life in a large sample of oldest-old primary care patients (85 +)” (AgeQualiDe). n = 648 individuals were included in the analyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…The differences in the assessment of QoL dependent on social support were also visible in the results obtained by Chruściel et al [41]-older people who lived with their families assessed the majority of the QoL domains significantly better than those who lived alone. According to Hajek et al [42], decreased social support was associated with higher possibility of developing problems in most of EuroQol-5D dimensions within individuals over time. Family routine activities and social participation may prevent functional deterioration and affects the QoL of the elderly [22].…”
Section: Discussionmentioning
confidence: 99%
“…The differences in the assessment of QoL dependent on social support were also visible in the results obtained by Chruściel et al [41]-older people who lived with their families assessed the majority of the QoL domains significantly better than those who lived alone. According to Hajek et al [42], decreased social support was associated with higher possibility of developing problems in most of EuroQol-5D dimensions within individuals over time. Family routine activities and social participation may prevent functional deterioration and affects the QoL of the elderly [22].…”
Section: Discussionmentioning
confidence: 99%
“…These data collectively indicate the emergence of the suppressor effect, a statistical phenomenon that is difficult to interpret ( 42 ). Some past studies have documented that cognitive function is largely unrelated to QoL in the oldest-old age on a multivariate level ( 21 , 43 ). Taken together, the observed negative linkage of intact cognition with “health” and “overall” should not be overinterpreted.…”
Section: Discussionmentioning
confidence: 99%
“…South-East Asia is one of the regions where the oldest-old age group shows the largest percentage increases. It is meaningful to study QoL of the oldest-old ( 21 ), especially in South-East Asia. Thus far, research on the factor structure and validity WHOQOL-AGE exclusively among the oldest-old is lacking.…”
Section: Introductionmentioning
confidence: 99%
“…Modern life has redefined living arrangements for most, as today more adults live alone and far from their families or origin [ 1 ]. The effects of these changes are especially pronounced for older adults with fewer social contacts [ 2 , 3 ]. This in turn affects both physical and mental health; in particular, depression, which is all too common in late life [ 4 , 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…This in turn affects both physical and mental health; in particular, depression, which is all too common in late life [ 4 , 5 , 6 ]. Previous research has shown that for older adults, social support serves as a protective factor [ 3 ] as the absence of social support increases the likelihood of depression [ 7 ]. Indeed, individuals with restricted social networks are at higher risk for depression [ 8 ].…”
Section: Introductionmentioning
confidence: 99%